Donor Recruitment for Fecal Microbiota Transplantation. Issue 7 (July 2015) - Paramsothy, Sudarshan; Borody, Thomas J.; Lin, Enmoore; Finlayson, Sarah; Walsh, Alissa J.; Samuel, Douglas; van den Bogaerde, Johan; Leong, Rupert W. L.; Connor, Susan; Ng, Watson; Mitchell, Hazel M.; Kaakoush, Nadeem; et al.
Abstract : Background: Increasing demand for fecal microbiota transplantation (FMT) has created a need for stool banks sourced from long-term healthy donors. Here, we describe our experience in recruiting and screening fecal donors. Methods: Mailbox, newspaper, and online advertisements were used. Potential donors were required to satisfy a prescreen telephone conversation, pass blood and stool investigations, then undertake a screening interview including medical history, physical examination, and evaluation of donor selection criteria. Results: One hundred sixteen potential donors were prescreened of whom 74 failed—47 declined based on study donation requirements (primarily related to frequency and duration of donations), 13 had medical comorbidities, 6 variant Creutzfeldt–Jakob disease risk factors, 8 for other reasons. Thirty-eight completed stool and blood testing—1 failed blood testing (indeterminate hepatitis C serology), whereas 15 failed stool investigations (5 Dientamoeba fragilis, 5 Blastocystis hominis, 1 B. hominis and D. fragilis, 1 Giardia intestinalis plus D. fragilis, 1 Norovirus plus Clostridium difficile toxin positive, and 2 leucocytes or erythrocytes on stool microscopy). Of the 18 potential donors proceeding to screening interview, 6 were excluded (3 body mass index >30, 1 illicit drug use, 1 uncontrolled anxiety and concerns regarding compliance, 1 irregular bowel movements after new medication commencement). In total, only 12 of 116 (10%) potential donors were enrolled as study donors. Conclusions: Recruitment of fecal donors for FMT is challenging with only a small percentage ultimately serving as donors. Many were unable or unwilling to meet the donor commitment requirements. A surprisingly large proportion of healthy asymptomatic donors failed stool testing, primarily due to gastrointestinal parasites. Abstract : Article first published online 28 April 2015.